(untitled) - Ervine, Cowan (New York, 2008)
This is an expert selection of statutes relating to company law designed to provide an easy-to-use reference whether in the lecture hall or in the examination. It contains the essential materials students need. It is published annually to ensure content is completely up-to-date. It excludes commentary and is therefore ideal for exam use. It is designed to be easy to use under exam conditions. It is compiled by an experienced lecturer
Keywords: Corporation law; Luật cổ phần công ty; European Union countries.,Liên Minh Châu Âu quốc gia